Design of a New Non-Singular Robust Control Using Synergetic Theory for DC-DC Buck Converter - Nettari, Yakoub; Kurt, Serkan (ISTANBUL UNIV-CERRAHPASA, 2018)
DC-DC converters control has gained much attention because of their broad uses in various fields, ranging from hand-held calculators to sophisticated airborne vehicles. Robustness in control systems, in spite of parametric variations, is an absolute requirement in many such applications. We propose a new controller to realize a robust performance despite the uncertainties on system parameter values. The controller employs an adaptive non-singular finite-time synergetic control method to tackle disturbances, which enhances the robustness and enables better performance during the transient phase compared to the terminal sliding mode control. A finite-time convergence is therefore achieved, while Lyapunov synthesis guarantees stability. Extensive simulation results of the DC-DC converter under harsh operating conditions confirm the effectiveness of the proposed controller.
Keywords: Synergetic control; finite time convergence; adaptive; DC-DC converter; sliding mode; SLIDING-MODE CONTROL; Engineering